2018
DOI: 10.2147/orr.s154289
|View full text |Cite
|
Sign up to set email alerts
|

The etiology, evaluation, and management of plantar fibromatosis

Abstract: Plantar fibromatosis (Ledderhose disease) is a rare, benign, hyperproliferative fibrous tissue disorder resulting in the formation of nodules along the plantar fascia. This condition can be locally aggressive, and often results in pain, functional disability, and decreased quality of life. Diagnosis is primarily clinical, but MRI and ultrasound are useful confirmatory adjuncts. Given the benign nature of this condition, treatment has historically involved symptomatic management. A multitude of conservative tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
42
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(56 citation statements)
references
References 35 publications
(92 reference statements)
0
42
0
Order By: Relevance
“…This condition usually progresses slowly and can cause pain, functional disability, and decreased quality of life. Although the etiology remains largely unknown, it is often associated with palmar and penile fibromatosis, which are known as Dupuytren's disease and Peyronie's disease, respectively [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…This condition usually progresses slowly and can cause pain, functional disability, and decreased quality of life. Although the etiology remains largely unknown, it is often associated with palmar and penile fibromatosis, which are known as Dupuytren's disease and Peyronie's disease, respectively [1][2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…Extracorporeal shock wave therapy (ESWT) has been used as a safe alternative treatment for chronic refractory musculoskeletal disease, such as plantar fasciitis Achilles tendinopathy and gluteal tendinopathy [10][11][12][13]. Previous studies have shown that ESWT also can be therapeutically applied to various forms of fibromatosis such as penile fibromatosis [14][15][16][17][18][19] and palmar fibromatosis [20][21][22] to reduce pain and soften nodules, although it did not affect the physical size of the nodules [3,15,16,19,23].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symptom management is often the treatment of choice for plantar fibromas due to the characteristically benign nature. Some of these treatments include custom or over-the-counter orthotics to help with weight bearing, steroid injections, verapamil, radiation, extracorporeal shock wave therapy, tamoxifen hormonal therapy, and collagenase, all with varying degrees of success and scientific data to back up the effectiveness [1,7].…”
Section: Treatment Optionsmentioning
confidence: 99%